Image Analysis of Urban Design Representation Towards Alternatives - Creagh, Robyn (2015)
This paper is a critical exploration of visual representation of urban places. This paper examines extracts from one Australian case study, the document An Urban Design Framework: A Vision for Perth 2050 (UDF), and makes comparisons between prior analysis of urban plans and the visual language of the UDF. Three alternative representations are then briefly discussed to explore some ways in which urban places are understood and communicated outside of urban design and planning frameworks. This paper is the start of a project rather than the culmination and sketches future directions of enquiry and possibilities for practice. The overall focus of this analysis is to reveal the way in which attitudes to place, roles and process are revealed through visual sections of city vision documents. The paper concludes that the visual representations in the UDF are not neutral and that these representations correspond to discursive traits seen in urban plans. These traits conceptualise place history as unproblematic and without authors, construct authority within technical process, and limit the role of place occupants as opposed to designer or planner. Parallel to moves to challenge the language of urban plans this paper illustrates that it is also important to challenge the visual language of urban design.